Efficacy and safety of clopidogrel versus aspirin monotherapy for secondary prevention in patients with coronary artery disease: a meta-analysis - Liu, Di; Xu, Wei Pan; Xu, Hang; Zhao, Lin; Jin, Dao Qun (Frontiers in Cardiovascular Medicine, 2023)
The benefits and risks of aspirin verse clopidogrel monotherapy in patients with coronary artery disease (CAD) remain controversial. This meta-analysis evaluated the efficacy and safety of aspirin verse clopidogrel monotherapy for long-term treatment in patients with CAD.Methods: Literature was searched in the Pubmed, the Cochrane Library, and the Embase databases until March 2023. The Cochrane Risk of Bias Tool was used to assess the risk of bias in included studies. Data were extracted from the included studies, heterogeneity analysis, and pooled analysis conducted by RevMan 5.3 software.Results: A total of five trials were included, involving 11, 766 patients with CAD. Compared with the aspirin group, the clopidogrel group was associated with reduced risk of major adverse cardiac and cerebrovascular events (MACCE) [risk ratio (RR)=0.68, P=0.0007], myocardial infarction (MI, RR=0.66, P=0.01), stroke (RR=0.58, P=0.003), and BARC major bleeding (RR=0.63, P=0.02). There were no significant differences in death from any cause (RR=1.06, P=0.59) and vascular death (RR=0.92, P=0.62) between the two groups.Conclusions: Patients with CAD use clopidogrel could further reduce the risk of MACCE, MI, stroke, and BARC major bleeding, compared with the use of aspirin. This finding supported the use of clopidogrel rather than aspirin in patients with CAD who required long-term antiplatelet monotherapy for preventing ischemic events.